Fracture Management of the Fifth Phalanx of the Cranial Dexter Extremity in Golden Retriever - Triyatmoko, Anang; Rickyawan, Nofan; Rifah Anggun (Media Kedokteran Hewan, 2023)
Fractures in animals are traumatic events that often occur. However, now the incidence of fractures can be well managed with the development of fixation techniques and various combination of anasthesia, as well as supporting equipment. This case study aims to determine the treatment of digiti fracture case, obtained from the Gaia Animal Clinic Surabaya. A ten-year-old Golden Retriever has a fractured the 5th digit of his righ cranial extremity. Radiographs, complete blood counts, blood chemistry, and electrocardiograms were taken to help confirm the diagnosis. The orthopedic surgery performed was internal fixation method using lag screw technique. Bone healing was evaluated by taken radiography and no complications were found. Wound healing was assisted by rehabilitation therapy using lasers. The 4th postoperative day, patient was discharged. Patient was able to walk even though he was still limping, the stitches were neatly closed, there was no seroma, around the stitches were swollen and redness.